Evaluation of Extra Axial Cerebellopontine Angle Tumours through MRI - Biswas, Prodip Kumar; Sardar, Md Hafiz; Saha, Gopal Chandra; Hossain, Mohammad Zaid; Hossain, Mohammed Shahadat; Paul, Tushit; Azad, Khan Abul Kalam (Journal of Dhaka Medical College, 2020)
Aim: This study aimed to evaluate the incidence of extra-axial cerebellopontine angle tumours and to characterize extra-axial cerebellopontine angle tumours. Methods: The study was carried out in Dhaka Medical College for the duration of 2 years from July 2016 to July 2018. All patients with clinical suspicion of CP angle tumours subjected 1.5 T MR imaging system. Total 30 patients were evaluated during this period. Results: Extra-axial CPA tumours accounts for 7-10% of brain tumours. Most common extraaxial CPA tumour is schwannoma (60%), followed by meningioma (27%), epidermoid (7%), arachnoid cysts (7%). 51-60 years is the most common age group involved. Schwannomas are common extra-axial CPA tumours which are enhancing round masses most commonly arise from the vestibular nerve and associated with enlargement of the internal auditory canal. Meningiomas are the second most common extra-axial CP angle tumours which oval or hemispheric lesions with a broad attachment to tentorium or petrous dura matter. Conclusion: MRI is the most sensitive noninvasive modality to characterize extra-axial CPA tumours. MRI identifies the location and extension of the lesions based on their characteristic signal and enhancement pattern on contrast. J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 104-107